1930
DOI: 10.1037/h0070355
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies in sex differences.

Abstract: Since 1927, the field here to be reviewed has opened up at an increasingly rapid rate. A good beginning can be made with Langdon-Davies' popular chapter on the " history of human ideas about sex differences " (79). Five factors are cited as causing the myth of the " female character," and a prophecy of the future of womankind is attempted. Sumner and Keller (124) present a vast amount of carefully gathered and documented data on the social side of sexual relations, especially in primitive man. Briffault (21), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1931
1931
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Allen (1) gives a thorough summary of recent literature on sex differences, including a section dealing with motor tests. To quote from him: "Motor learning has hitherto shown large sex differences, as in the Young slot maze, e.g.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Allen (1) gives a thorough summary of recent literature on sex differences, including a section dealing with motor tests. To quote from him: "Motor learning has hitherto shown large sex differences, as in the Young slot maze, e.g.…”
Section: Previous Studiesmentioning
confidence: 99%
“…This matter of sex differences in various types of performance has been a topic of ceaseless interest, both in speculation and in experimentation. Allen (1,2) and Miles and Terman (4) have summarized recent literature on this topic from two different angles. Popular opinion on the subject varies in its expression of possible differences.…”
mentioning
confidence: 99%
“…More than a century after the publication of the first systematic studies (see Allen, ; Thompson, ), sex differences in personality continue to be passionately debated. Taken as groups, do men and women show substantially different patterns of feelings, thoughts, and behaviors?…”
Section: Introductionmentioning
confidence: 99%
“…During a half century or more of experimental psychology many studies have been made to ascertain whether man is intellectually superior or inferior to woman. Although the earliest attacks on this complicated problem yielded somewhat equivocal data, results from the more recent studies, particularly those in which opportunities have been rigidly equated, have consistently indicated that truly significant differences between measurable intellectual performances of men and women are exceptional rather than the rule (1,4,5). Furthermore, if sporadic differences are found they are usually explainable by the supposition that the tests used are specific for an acquired interest or intellectual skill that, because of unequal opportunity or application, was more highly developed in the sex to which the superiority pertained.…”
mentioning
confidence: 99%